If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3=(2/7+x)
We move all terms to the left:
3-((2/7+x))=0
Domain of the equation: 7+x))!=0We add all the numbers together, and all the variables
We move all terms containing x to the left, all other terms to the right
x))!=-7
x!=-7/1
x!=-7
x∈R
-((+x+2/7))+3=0
We multiply all the terms by the denominator
-((+x+2+3*7))=0
We calculate terms in parentheses: -((+x+2+3*7)), so:We get rid of parentheses
(+x+2+3*7)
We add all the numbers together, and all the variables
(x+23)
We get rid of parentheses
x+23
Back to the equation:
-(x+23)
-x-23=0
We add all the numbers together, and all the variables
-1x-23=0
We move all terms containing x to the left, all other terms to the right
-x=23
x=23/-1
x=-23
| 10q+2q-12q+2q=8 | | 1.3-3.3x=12.7-1.3x | | 15p+p-6p-p-4p=5 | | 17k-13k=16 | | X(X-17)-18x=(x-5)(x+16) | | 80x-16x^2-96=0 | | 50=3(s+16)-2(s-2 | | w+5/6=4 | | u/9+43=51 | | 1+5/3=(7/3x) | | (x-40)/(x)=(1/6) | | 6(z+10)=96 | | 60(z+10)=96 | | (-3+7i)-(14-6i)=17+1 | | 2=2(k-49) | | 20-3z=11 | | (2x+56)=(6x+8) | | 12=w/4=10 | | 8(x+9/5)=-48/5 | | 6x+9/2=-27/2 | | -3x/(4)-2=-35/4 | | -3x/4-2=-35/4 | | 36n=72+5 | | 9x2+18x−11=0 | | 6(x-7)+2=-88 | | q-(47/6)=(13/2) | | 5(x+6)+3=18 | | -5(v-1)=-2v-16 | | (3x+10=22) | | 75-x+57+2x=0 | | 2-10n+5n=10-88 | | (3)x=3/5 |